2021
DOI: 10.1097/jmq.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LACE and HOSPITAL Readmission Risk Scores for CMS Target and Nontarget Conditions

Abstract: This study evaluated the utility and performance of the LACE index and HOSPITAL score with consideration of the type of diagnoses and assessed the accuracy of these models for predicting readmission risks in patient cohorts from 2 large academic medical centers. Admissions to 2 hospitals from 2011 to 2015, derived from the Vizient Clinical Data Base and regional health information exchange, were included in this study (291 886 encounters). Models were assessed using Bayesian information criterion and area unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Validated readmission prediction models are used in health care, such as the LACE index and HOSPITAL scores. 20 - 23 However, these models do not perform well in patients with cancer, as shown recently in a study by Jones et al, 48 where both LACE and HOSPITAL underperformed in patients with colon and lung cancers relative to the general population. This highlights the importance and the need for cancer-specific models.…”
Section: Discussionmentioning
confidence: 89%
“…Validated readmission prediction models are used in health care, such as the LACE index and HOSPITAL scores. 20 - 23 However, these models do not perform well in patients with cancer, as shown recently in a study by Jones et al, 48 where both LACE and HOSPITAL underperformed in patients with colon and lung cancers relative to the general population. This highlights the importance and the need for cancer-specific models.…”
Section: Discussionmentioning
confidence: 89%
“…showed that the "LACE and HOSPITAL readmission risk-prediction algorithms performed well and equivalently in a heterogeneous and diverse population." 24,25 It is important to note that during the study period of 2014-2019, the observed average annual 30-day readmission rate in the study facility varied from 10.2% to 12.7% as compared with the observed national average of 18.4% in 2016, for example. 26 The low rates of readmission in the study facility likely reflect multiple interventions enacted to reduce readmissions, for example, increased use of intravenous therapies, increased on-site diagnostic interventions, and other systematic changes designed to increase the diagnosis and treatment of patients in place.…”
Section: Discussionmentioning
confidence: 93%
“…As shown in Figure 2, our study further indicates a greater risk of readmission within 30 days with rising LACE and HOSPITAL scores. This is supported by the 2021 study by Staples et al, which demonstrated that “mLACE+, LACE+ and LACE scores predicted hospital readmission with excellent calibration and adequate discrimination,” and the 2022 study by Jones et al, which showed that the “LACE and HOSPITAL readmission risk‐prediction algorithms performed well and equivalently in a heterogeneous and diverse population.” 24,25 It is important to note that during the study period of 2014–2019, the observed average annual 30‐day readmission rate in the study facility varied from 10.2% to 12.7% as compared with the observed national average of 18.4% in 2016, for example 26 . The low rates of readmission in the study facility likely reflect multiple interventions enacted to reduce readmissions, for example, increased use of intravenous therapies, increased on‐site diagnostic interventions, and other systematic changes designed to increase the diagnosis and treatment of patients in place 27 .…”
Section: Discussionmentioning
confidence: 98%
“…Ademais, são identificados estudos voltados exclusivamente para a análise da readmissão de coorte de pacientes com câncer, como por exemplo o câncer de cólon e pulmão (JONES et al, 2022) e de pacientes submetidos a procedimentos cirúrgicos decorrentes do câncer, como pacientes com tumor cerebral (CAPLAN et al, 2019;WINTER et al, 2020), câncer de bexiga (SALUK et al, 2018) e câncer colorretal (ALYABSI et al, 2022).…”
Section: Discussionunclassified